Influence of metabolic indicators, smoking, alcohol and socioeconomic position on mortality after breast cancer. (May 2015) - Larsen, Signe Benzon; Kroman, Niels; Ibfelt, Else Helene; Christensen, Jane; Tjønneland, Anne; Dalton, Susanne Oksbjerg
Abstract Background. Factors differently distributed among social groups like obesity, metabolic syndrome, diabetes, smoking, and alcohol intake predict survival after breast cancer diagnosis and therefore might mediate part of the observed social inequality in survival. Material and methods. We conducted a cohort study among 1250 postmenopausal breast cancer patients identified among 29 875 women in the Danish Diet, Cancer and Health Study. Participants completed questionnaires and anthropometric measurements were made at enrollment. Information on survival, socioeconomic position, and comorbidity was obtained by linkage to national Danish registries. Clinical information was obtained from the nationwide Danish Breast Cancer Database. Selected information was obtained from hospital records at time of diagnosis. All analyses were based on Cox proportional hazard models, using death from all causes as outcome. Results. Median follow-up was 9.6 years [interquartile range (IQR), 2.2–17.0 years]. The hazard ratio (HR) for death from all causes increased with lower education (p for trend, 0.01). Adjustment for disease-related prognostic factors, comorbidity and metabolic indicators measured as BMI, waist circumference and diabetes, and smoking and alcohol affected but did not explain the social gradient. Conclusion. The findings indicate that these factors explain some but not all the social inequality in survival after breast cancer and that improvement of lifestyle to some extent would improve survival among women with low socioeconomic position.